2019
DOI: 10.1302/0301-620x.101b7.bjj-2019-0215.r1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and satisfaction following arthroscopic rotator cuff repair

Abstract: Aims The aim of this study was to investigate the influence of age on the cost-effectiveness of arthroscopic rotator cuff repair. Patients and Methods A total of 112 patients were prospectively monitored for two years after arthroscopic rotator cuff repair using the Disabilities of the Arm, Shoulder and Hand questionnaire (DASH), the Oxford Shoulder Score (OSS), and the EuroQol five-dimension questionnaire (EQ-5D). Complications and use of healthcare resources were recorded. The incremental cost-effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…In clinical practice, although patients undergoing single-stage repair needed help with shoulder pad replacement and passive exercise, and some patients slept uncomfortably throughout the night in the early postoperative period, they could adapt and overcome difficulties gradually. We considered that letting patients know the advantages and disadvantages of different surgical options by preoperative conversation was important [31]. Patients in single-stage group have been prepared mentally for difficult postoperative rehabilitation, and one-time recovery was their expectation.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, although patients undergoing single-stage repair needed help with shoulder pad replacement and passive exercise, and some patients slept uncomfortably throughout the night in the early postoperative period, they could adapt and overcome difficulties gradually. We considered that letting patients know the advantages and disadvantages of different surgical options by preoperative conversation was important [31]. Patients in single-stage group have been prepared mentally for difficult postoperative rehabilitation, and one-time recovery was their expectation.…”
Section: Discussionmentioning
confidence: 99%
“…The average FS-OSS score was 24.23 ± 9.11 initially and 24.04 ± 8.75 in the retest taken 5 to 7 days later, with the median (interquartile range) being 24 (18-32) and 24 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The average initial SC-OSS was 25.56 ± 9.98, and it was 24.78 ± 9.51 during retesting, with the median (interquartile range) values of 25 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and 24 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)…”
Section: Reliabilitymentioning
confidence: 98%
“…25 The Oxford Shoulder Score (OSS) is an internationally recognized assessment instrument to assess the pain perception and quality of life in patients with shoulder pain and to evaluate the effectiveness of different treatments. 23,24 After its original English version was published in 1996, 6 it has been translated into many languages in different cultural settings to communicate internationally. 2,3,[8][9][10][11][12]17,21,22,[29][30][31][32] In 2015, a simplified Chinese version of OSS (SC-OSS) was developed by Xu et al 39 Even so, high illiteracy and low income in the developing countries may limit the applicability of the OSS.…”
mentioning
confidence: 99%
“…Nicholson et al 43 used the EQ-5D in a prospective study to determine the value of RCR in patients with massive RCTs. They found that arthroscopic RCR led to a mean improvement in the EQ-5D from 0.54 at baseline to 0.81 at one year ( P < .001) and 0.86 at two years ( P = .08).…”
Section: Review Of Shoulder Literaturementioning
confidence: 99%